Electron-helium scattering in Debye plasmas - Zammit, Mark; Fursa, Dmitry; Bray, Igor; Janev, R. (American Physical Society, 2011)
Electron-helium scattering in weakly coupled hot-dense (Debye) plasma has been investigated using the convergent close-coupling method. The Yukawa-type Debye-Hückel potential has been used to describe plasma Coulomb screening effects. Benchmark results are presented for momentum transfer cross sections, excitation, ionization, and total cross sections for scattering from the ground and metastable states of helium. Calculations cover the entire energy range up to 1000 eV for the no screening case and various Debye lengths (5–100 a0). We find that as the screening interaction increases, the excitation and total cross sections decrease, while the total ionization cross sections increase.